Clearfield, Douglas County - Sturm, Christopher (Kansas State University, The Chapman Center for Rural Studies, 2013)
German families formed the community of Clearfield in Douglas County, Kansas, in the 1850s, united by language and religion. This study overviews a collection of photographs, maps, and documents detailing the history of the Clearfield Community in Palmyra Township, Douglas County, Kansas.
Christopher Sturm, “Clearfield, Douglas County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/143.
Keywords: Douglas County; George Sturm; Captain's Creek; Clearfield United Methodist Church; German Settlers; Palmyra Township